Thermogravimetric and Morphologic Analysis of Oxo-degradable Polyethylene Films after Accelerated Weathering. Issue 1 (February 2013) - Klein, Jalma Maria; Ramos, Gustavo Roberto; Grisa, Ana Maria Coulon; Brandalise, Rosmary Nichele; Zeni, Mara
The degradation of polyethylene films containing a prodegradant additive has been studied after exposure to accelerated weathering for 480 hours. After exposure, the effects of photo-oxidation were evaluated by thermogravimetry, infrared spectroscopy and X-ray diffraction. The kinetics of the thermo-oxidative degradation of polyethylene films, with and without the prodegradant additive, was assessed by applying the Flynn-Wall-Ozawa method to thermogravimetric analysis carried out at different heating rates. The values of activation energy for samples with and without the prodegradant additive were in the range of 166-214 kJ/mol, and increased, after exposure to accelerated weathering, to values in the range of 245-279 kJ/mol. After exposure, the crystallinity index increased by 9 percentage points for the polyethylene sample without the prodegradant additive and by 8 percentage points for the sample containing the prodegradant additive. For both samples exposed to accelerated weathering, an increase in the carbonyl index was observed. The use of the prodegradant additive caused more evident changes in the crystalline regions of the polymer than in the amorphous regions; the results of this study are thus important from the standpoint of degradation, since the crystalline regions are considered difficult to degrade.